Prevalence, Patterns, and Persistence of Sleep Problems in the First 3 Years of Life - Byars, Kelly C. (American Academy of Pediatrics, 2012)
OBJECTIVE: Examine the prevalence, patterns, and persistence of parent-reported sleep problems during the first 3 years of life. METHODS: Three hundred fifty-nine mother/child pairs participated in a prospective birth cohort study. Sleep questionnaires were administered to mothers when children were 6, 12, 24, and 36 months old. Sleep variables included parent response to a nonspecific query about the presence/absence of a sleep problem and 8 specific sleep outcome domains: sleep onset latency, sleep maintenance, 24-hour sleep duration, daytime sleep/naps, sleep location, restlessness/vocalization, nightmares/night terrors, and snoring. RESULTS: Prevalence of a parent-reported sleep problem was 10% at all assessment intervals. Night wakings and shorter sleep duration were associated with a parent-reported sleep problem during infancy and early toddlerhood (6–24 months), whereas nightmares and restless sleep emerged as associations with report of a sleep problem in later developmental periods (24–36 months). Prolonged sleep latency was associated with parent report of a sleep problem throughout the study period. In contrast, napping, sleep location, and snoring were not associated with parent-reported sleep problems. Twenty-one percent of children with sleep problems in infancy (compared with 6% of those without) had sleep problems in the third year of life. CONCLUSIONS: Ten percent of children are reported to have a sleep problem at any given point during early childhood, and these problems persist in a significant minority of children throughout early development. Parent response to a single-item nonspecific sleep query may overlook relevant sleep behaviors and symptoms associated with clinical morbidity.